anonymous
  • anonymous
6x + 22 = A(x + 2) + B(x - 4) ^I am doing partial fraction decomposition and this is what I am at. Attempt: "Trick" Let x = -2. Then, 6(2) + 22 = A(-2 + 2) + B(-2 - 4) 12 + 22 = 0 + B(-6) 34 = -6B -34/6 = B ------ "No Trick" 6x + 22 = Ax + 2A + Bx - 4B (LHS = RHS, then coeff's are equal), 6 = A + B, [1] 22 = 2A - 4B => 11 = A - 2B, [2a] [2a] - [1], 5 = 0 -B => -5 = B. Why aren't the two answers the same?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
i am lost. where does this line come from \[6x + 22 = Ax + 2A + Bx - 4B\]
anonymous
  • anonymous
oh nvm i see the mistake
anonymous
  • anonymous
6x + 22/(x+2)(x-4) dx

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
What is the mistake?
anonymous
  • anonymous
Let x = -2. Then, 6(2) + 22 = A(-2 + 2) + B(-2 - 4)
anonymous
  • anonymous
should be Let x = -2. Then, 6(-2) + 22 = A(-2 + 2) + B(-2 - 4)
anonymous
  • anonymous
Ok I actually did it with -2, and then this is what I got: 6x + 22 = A(x + 2) + B(x-4). Let x = -2. Then, 6(-2) + 22 = A(-2 + 2) + B(-2-4) -12 + 22 = B(-6) 10/6 = -B -10/6 = B....
anonymous
  • anonymous
6x+22=(a+b)x+(2a-4b) now comparing both sides 6=a+b 22=(2a-4b) now solve two equations you will get a and b
anonymous
  • anonymous
@SUROJ I did that for "No Trick"
anonymous
  • anonymous
\[a+b=6\] \[a+2b=11\] \[b=5\]
anonymous
  • anonymous
What am I doing wrong wrt the trick? Why am I not getting the same answer as the second method?
.Sam.
  • .Sam.
(6x+22)/((x+2)(x-4)) Factor out the 2, 2(3x+11)/((x+2)(x-4)) ---------------------------------------- A/(x+2)+B/(x-4) ---------------------------------------- 6=A+B 22=-4A+2B ---------------------------------------- A=-5/3 B=23/3 -(5)/(3(x+2))+(23)/(3(x-4))
anonymous
  • anonymous
i see mistake when you put 6(2) in place of 6(-2) ....in first trick
anonymous
  • anonymous
did you see that?
anonymous
  • anonymous
ok lets start at the top is it \[\frac{6x + 22 }{(x+2)(x-4)}=\frac{a}{x+2}+\frac{b}{x-4}\]
anonymous
  • anonymous
Ok folks, the point here is that the "Trick" does not match with "No Trick" for the below solution: 6x + 22 = A(x + 2) + B(x-4). Let x = -2. Then, 6(-2) + 22 = A(-2 + 2) + B(-2-4) -12 + 22 = B(-6) 10/6 = -B -10/6 = B....
anonymous
  • anonymous
@satellite73 Yes
anonymous
  • anonymous
Let x = -2. Then, 6(2) + 22 = A(-2 + 2) + B(-2 - 4) || in this step 12 + 22 = 0 + B(-6) 34 = -6B -34/6 = B
anonymous
  • anonymous
@SUROJ Look at my recent one
anonymous
  • anonymous
that's right
anonymous
  • anonymous
Then why is it NOT the same as "No trick"?
anonymous
  • anonymous
ok so we can do this by writing \[6x+22=A(x+2)+B(x-4)\] \[-12+22=-6B\] \[10=-6B\] \[-\frac{5}{3}\] and likewise \[A=\frac{23}{3}\] so give \[\frac{6x+22}{(x+2)(x-4)}=\frac{23}{3(x+2)}-\frac{5}{3(x+4)}\]
anonymous
  • anonymous
a+b=6 is same as 2(a+b)=2(6) is same as 2a+2b=12 is same as -2a -2b =-12 add -2a-2b=-12 and 2a-4b=22
anonymous
  • anonymous
Alright, then how about the "No trick"?
anonymous
  • anonymous
typo on last line should be \[\frac{6x+22}{(x+2)(x-4)}=\frac{23}{3(x+2)}-\frac{5}{3(x-4)}\]
anonymous
  • anonymous
add left left and right right -2a-2b=-12 and 2a-4b=22 gives -6b=10 so b is -10/6 same as first one
anonymous
  • anonymous
now we try with "no trick" \[6x+22=A(x-4)+B(x+2)\] \[6x+22=Ax-4A+Bx+2B\] \[6x+22=(A+B)x+2B-4A\] \[A+B=6\] \[2B-4A=22\]
anonymous
  • anonymous
i get the same answer solving this one
anonymous
  • anonymous
yes.....

Looking for something else?

Not the answer you are looking for? Search for more explanations.